PERANCANGAN STUDIO DIGITAL IMAGING “IMAGINE” - Tommy Himawan; Hutomo Setia Budi (Universitas Ciputra Surabaya, 2016)
Since the emergence of social media, especially instagram image’s quality become an attention, it had a positive impact on the development of photography and other things that support such as photo studios, photographers, and camera. However, the camera certainly has limitations on the result, the sharpness of the colors and the dimensions of the resulting image from the camera can be maximized and some photographers may not be particularly good at editing especially digital imaging. Therefore this study aimed to design a digital imaging studio. The study was conducted with qualitative, quantitative and literature studies. Results of the study are expected in the form of digital imaging studio focused in terms of editing, compositing, and modification of visual elements in the final image.